Psycho-social characterization of the fi rst category “A” football players of the Colombian Professional Football - Orrego Ramírez, Lina María; Velásquez Restrepo, Jorge Iván; Uribe Lopera, Lucas (Pensando Psicología, 2010)
The imperious need to know the one who is our professional football player, the group of investigation: “sport and society”, of the Andean School of the Sport belonging to the Cooperative University of Colombia, Medellin sectional, designed an investigation that had objective how characterized the professional Colombian football player belonging to the category first “A”. The investigation centered his attention on four fundamental aspects of the sportsman: the demographic one (the sportsman with relation to his environment), the individual (the sports-man with relation to if same as (like) being a human being), the affective associate (the sportsman with regard to his interpersonal relations) and the professional (the sportsman with relation to the sport that it (he, she) recovers (plays)). The results are those that they present in the present article.